High rate of multidrug-resistant Escherichia coli isolated from ready to eat: crispy fried chicken in Jember: a real threat to human health - Suswati, Enny; Supangat (BKM Public Health and Community Medicine, 2024)
Purpose: This study was conducted to assess prevalence and antibiotic resistance profile of E. coli from ready-to-eat crispy fried chicken (CFC) in Jember city, Indonesia. Methods: This cross-sectional study was conducted from November 2020 to April 2021 by collecting a total of 81 CFC samples from 27 food stalls in campus area using a simple random sampling method. Isolation and determination of E. coli use were performed by conventional culture method and an antibiotic susceptibility test was conducted by using Kirby Bauer disk diffusion method on the Mueller–Hinton agar. Result: Out of 81 CFC samples, 77 (95.06%) were positive for E. coli. High E. coli drug resistance was observed on ampicillin, amoxicillin, (100%) followed by cefixime (98.72%), erythromycin (97.59%), sulfamethoxazole (93.59%), azithromycin (83.33%), cefotaxime (78.28%), chloramphenicol (75.64%), and cefixime (74.36%). On the other hand, there was the highest susceptibility for ciprofloxacin (64.10%). Multidrug resistance was also found in 76/77 (98.70%) of the isolates. MAR index was 0.4-1. Conclusion: The resistance pattern CfmCroAmlAmpAzmCtxSxtCE was the most common among the E. coli isolates, with 17 showing it. The multiple antibiotic index (MAR index) ranged from 0.4 to 1. Hygienic measures should be rigorously implemented, and monitoring resistance of E. coli is required to reduce the risks related to the emergence of multi-resistant bacteria.